Pengaruh Capital Intensity, Manajemen Laba , Dan Likuiditas Terhadap Agresivitas Pajak Pada Perusahaan Property Dan Real Estate Yang Terdaftar Pada Bursa Efek Indonesia 2017-2022 - Sutanto, Hermawan; Shaputra, Juliandi; Henson, Henson (Politeknik Negeri Ambon, 2024)
This study aims to examine the effect of Capital intensity, Earnings Management, and Liquidity on Tax Aggressiveness in Property and Real Estate Companies listed on the IDX 2017-2022. In this study, tax aggressiveness is measured using the effective tax rate (ETR). This type of research is quantitative using secondary data sources in the form of annual financial reports or annual reports through the Indonesian Stock Exchange (IDX). The population used in this study are companies engaged in property and real estate listed on the Indonesia Stock Exchange (IDX) starting from 2017-2022. The sampling technique in this study used purposive sampling with several criteria determined to obtain 14 companies with 84 data obtained. Data analysis techniques using Descriptive Statistics, Classical Assumption Test, Multiple Linear Regression Test, and Hypothesis Test using the SPSS 25 program. The results of this study indicate that partially Capital Intensity has a negative and significant effect on Tax Aggressiveness, partially Earnings Management has no effect on Tax Aggressiveness, and partially Liquidity has a positive and significant effect on Tax Aggressiveness. The results of the study simultaneously show that Capital Intensity, Earnings Management, and Liquidity have a significant effect on Tax Aggressiveness in property and real estate companies listed on the Indonesia Stock Exchange 2017-2022. Keywords: Capital Intensity, Earnings Management, Liquidity